Analisis Teologis Kontekstualisasi Film Kartun Tujuh Malapetaka Wahyu 14-18 - Hotma S. P. Silitonga (Fakultas Filsafat Universitas Advent Indonesia, 2013)
The seven plagues in Revelation 14-18 which will take place in the future are often presented as a threat to people in this scary world. The book of Revelation in reality is the summary and conclusion of The Story Of Redemption from Genesis up to the Letter of Jude.Â All of these “were written to teach and encourage us by giving us hope” (Romans 15:4, Contemporary English Version). Based on this historical fact, the reality of cartoon film of the seven plagues which Apostle John has seen about 2000 years ago should be benefited to us as “a counsel of peace to us from the Lord” (2 Timothy 3:14-17).Â The Word of The Lord “should be interpreted by the Lord Himself because He is The Author of The Worrd of Truth” (John 14:26; 16:13; 2 Peter 1:19-21).Â The real contemporer meaning of cartoon film of the past in Revelation is the “reality of hell burning heart of sin” during oeu daily life (Hosea 7:6).